Contribution to the diversity of soil mites (Acari, Gamasida) in southern Croatia (Dalmatia), with some ecological and zoogeographical notes - Kaczmarek, Sławomir; Marquardt, Tomasz (Biological Letters, 2011)
The species diversity of soil gamasid mites (Acari) in southern Croatia (Dalmatia) was studied in August 2002. In the Krka National Park, Brač Island, and near the town of Makarska, 320 samples were collected from various microhabitats: soil, grass and moss ground cover, wet moss, needle litter, moss covering tree trunks, and decaying wood). Altogether, 2097 mites of 56 gamasid species were recorded. Dominant species were: Polyaspis patavinus (Brač Island), Zercon fageticola (Makarska), and Cheiroseius serratus (Krka National Park). Analyses of ecological preferences and zoogeographic distribution were made for Polyaspis patavinus, Cheiroseius serratus, Zercon fageticola, Z. berlesei, Z. athiasi, Asca nova and A. aphidioides.